Implementation of Instructional Explicit Model toward Writing Skill of Descriptive Text for Junior High School Student - Refa Lina Tiawati; Suci Dwinitia (ppjbsip, 2019)
Indonesian language learning Curriculum 2013 which will be studied by junior high school students is one of them is description text. Description text is a type of text describing an object, a thing and a situation so that the reader seems to hear seeing, or feeling the things described. In writing description text, it must pay attention to the structure and rules of language of the description text that have been set, so as to produce a solid and intact description text. In writing the description text students still experience difficulties in writing language rules that are still lacking. The purpose of this study was to determine the effect of using the Explicit Instruction model on the description of writing skills in junior high school students. This type of research is quantitative research using the experimental method. The design of this study was one group pretets-posttest design of this study conducted twice before being given treatment and after being given treatment. The sampling technique of this study was purposive sampling technique, the sample in this study was one class. The data in this study is a performance test results of the description text writing skills before and after using the Explicit Instruction learning model for the description skills of text writing for junior high school students. The results of his research are that there is a significant effect between the learning model and the results of the news text writing skills before and after using the Explicit Instructionmodel on Writing Skills. Text description for Junior High School Students. This is evidenced by the results of research that show that the value of tcount> t table (> 1.90), so that H0 is rejected and H1 is accepted. That means the explicit instruction learning model is effectively used in the description writing skills of junior high school students.